Analisis Visual Storytelling pada Primaku Sebagai Aplikasi Monitoring Tumbuh Kembang Anak - Haq, Munqizul Dienul; Rahman, Yanuar; Tohir, Mohamad (Visualita Jurnal Online Desain Komunikasi Visual, 2024)
The growth and development of children is now one of the challenges for parents, especially those who do not have much time to be with their children, so some parents do not know how far their children grow and develop. Although some parents have a fairly divided time for their work, they are not hands-off, recorded 16 thousand parental ratings on the PrimaKu application prove that those who lack time with children are still very concerned about their development and growth. The Primaku application is designed to help parents who have a lot of work outside and do not have much time with their children, even if parents entrust their children to caregivers, they can see the growth and development of their children anytime and anywhere through smartphones. This research uses qualitative methods, using visual storytelling theory which will be a new trigger for the PrimaKu application, the use of visual stroytelling analysis will be a solution to increase the audience and desire of parents to use the application to accompany the growth and development of children.